Tilt-shift photography: motherhood portrayed in Anne Enright’s Taking pictures - Eufrausino (USP), Caroline Moreira; Izarra (USP), Laura Patrícia Zuntini de (ANTARES: Letras e Humanidades, 2013)
"Tilt-shift photography" is used when referring to camera movements: when this artifact is used, the photographer is able to change the tilt and redefine the picture focus. Considering this technical characteristic of photography, it aims to analyze the collection Taking Pictures by the Booker Prize Winner's Anne Enright. Born in Ireland, Enright portrays many of the tensions women face regarding motherhood taking into account the perfection attributed to the Irish mother figure in social and cultural history. The analysis aims to introduce the authoress, contextualize her works and verify the role of the mother in contemporary Irish society through her short stories. In what follows, I read the contemporary Irish writer Anne Enright as a photographer and the pictures are the short stories